Epêntese vocálica em encontros consonantais por falantes brasileiros de inglês como língua estrangeira - Nascimento, Geisibel Cristina Andrade [UNESP] (2015)
This Master's thesis aims to analyze the insertion of epenthetic vowel in consonant clusters in the pronunciation of the English language by Brazilian learners. The aspect analyzed in this research refers to the difficulty that English language students have to produce the consonant sounds, especially those which are not part of the phonological system of their mother language, Brazilian Portuguese, or that are not used similarly. The corpus was composed by words, which contain, in onset and/or coda position, segments or sequences of segments that are different from those found in Brazilian Portuguese in order to check how English learners would produce them. We selected 46 words from Longman Communication 3000, a list of the 3,000 most repeated words in English. We have asked 30 English students, from different levels of proficiency (basic, intermediate and advanced) to read the selected words aloud. The reading was recorded and, from the recordings, phonetic transcriptions of the informants' pronunciation were done for each word. From these transcriptions, it was possible to make the analysis about the production of each informant. A statistical analysis was done to verify the frequency of the insertion of the epenthetic vowel in order to correct the structures of the English language, which are not familiar to the learner, i.e., those ones that are not part of their mother language. After that, the data were analysed considering the Optimality Theory to see how the constraints behave in a foreign language learning. We concluded that the insertion of the epenthetic vowel is a strategy that is frequently used in the pronunciation of English words that has segments and/or sequences of segments in onset or coda position which are different from those that are found in Brazilian Portuguese. However, the epenthesis is not the only one. The palatalization of /t/ and /d/ and the aspiration of /p/, /t/ and /k/ were frequently used too ...